2022
DOI: 10.3389/fmars.2022.936028
|View full text |Cite
|
Sign up to set email alerts
|

Estimating ecological carrying capacity for stock enhancement in marine ranching ecosystems of Northern China

Abstract: Marine ranching has been proposed as a promising solution to manage the depleted coastal fishery ecosystem in recent decades across China. Marine ranching integrates the practices of artificial habitat-based with aquaculture-based enhancement. Assessing the ecological carrying capacity of target species for enhancement is a precondition for determining the optimal numbers for release, particularly for those species whose habitat restrictions have been eliminated through the construction of artificial habitats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Therefore, it is easier to realize the scale effect of ecological conservation in the southern marine pasture. From the perspective of the specific operation of marine ranches, the initial cost input and artificial reef input of marine ranches in northern China are unreasonable, and the operation and management bodies are mostly enterprises, which are more likely to produce economic benefits rather than ecological benefits [51]. On the other hand, the model of the proliferation, release, and environmental restoration of marine pastures in the south is more likely to bring ecological benefits and realize intensive management [19].…”
Section: Heterogeneity Analysis Of the Impact Of The Establishment Of...mentioning
confidence: 99%
“…Therefore, it is easier to realize the scale effect of ecological conservation in the southern marine pasture. From the perspective of the specific operation of marine ranches, the initial cost input and artificial reef input of marine ranches in northern China are unreasonable, and the operation and management bodies are mostly enterprises, which are more likely to produce economic benefits rather than ecological benefits [51]. On the other hand, the model of the proliferation, release, and environmental restoration of marine pastures in the south is more likely to bring ecological benefits and realize intensive management [19].…”
Section: Heterogeneity Analysis Of the Impact Of The Establishment Of...mentioning
confidence: 99%
“…Previous studies have shown that fluid shear stress caused by waves and tides affects the transport, attachment and recruitment of marine organism larvae (Shanks et al, 2003;Bolle et al, 2009;Reidenbach et al, 2009;Whitman and Reidenbach, 2012;Hou et al, 2022), while water temperature and salinity directly affect larval feeding and development (Zimmerman and Pechenik, 1991;Nurdiani and Zeng, 2007;McGeady et al, 2021). Existing research and the Chinese technical specifications for the stock enhancement indicate the appropriate growth conditions for PTL (China, 2014;Ge, 2019;Wang et al, 2022), as shown in the Table 1 below.…”
Section: Habitat Suitability Model For Portunus Trituberculatus Larvaementioning
confidence: 99%
“…Many countries have adopted fisheries management measures to address the current decline of marine fisheries resources, including establishing fishing quotas, marine reserves, and stock enhancement (Roberts et al, 2005;Nielsen and Holm, 2007;Colloca et al, 2013;Green et al, 2014). Among them, stock enhancement programs, with their effective ecosystem restoration function and advantage in alleviating the scarcity of fishery resources, are considered to be an important measure for restoring fishery resources (Taylor et al, 2005;Purcell et al, 2012;Han et al, 2016;Wang Z. et al, 2022). Stock enhancement refers to the breeding and release of fish, shrimp, shellfish, algae, and other aquatic organisms into natural waters to allow for their natural growth, in order to increase the population size of marine species, rebuilt biomass of the fished stock, attempting to restore ecological balance (Lorenzen et al, 2010;Hilborn et al, 2020;Pilnick et al, 2021).…”
Section: Introductionmentioning
confidence: 99%